Ultrahigh-temperature carbon-based high-entropy ceramic coating and preparation method thereof
By introducing carbon-based materials and specific oxides into high-entropy ceramic coatings and depositing the coatings using plasma spraying technology, the problem of insufficient oxidation and adhesion of existing ceramic coatings in high-temperature environments is solved, and higher wear resistance and stability are achieved.
Patent Information
- Application Number
- CN202510387208.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-entropy ceramic thermal barrier coatings still have room for improvement in oxidation resistance and adhesion.
Ultra-high temperature carbon-based high-entropy ceramic coating is used, and the composition includes mixed slurry, rare earth oxide, metal oxide and fluorinated graphene oxide, which is deposited on the substrate surface by plasma spraying physical vapor deposition technology.
It significantly improves the wear resistance, oxidation resistance and adhesion of ceramic coatings, and can maintain structural integrity and stable performance under high temperature environments.
Smart Images

Figure CN119899996A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic coatings, and in particular to an ultra-high temperature carbon-based high entropy ceramic coating and a preparation method thereof. Background Art
[0002] High entropy ceramics are a new type of multi-component (five or more components) single-phase solid solution ceramics with a high entropy value. Compared with traditional ceramics, high entropy ceramics have the characteristics of high strength, hardness, good wear resistance and structural stability. The Chinese patent with publication number CN116377372B discloses a high entropy ceramic thermal barrier coating and its preparation method. The chemical formula of the high entropy ceramic thermal barrier coating is (Y 0.2 Sm 0.2 Eu 0.2 G 0.2 Yb 0.2 )2Zr2O7, where the percentage of the molar number of each rare earth element to the total molar number of all rare earth elements is 18% to 22% respectively. The elements in the high entropy ceramic thermal barrier coating are evenly distributed on the coating without element segregation, and have a fluorite phase structure, and the cross-sectional morphology is a feather-shaped columnar high strain tolerance structure; the bottom coating is composed of columnar main crystals and dendrite sequences, with a large porosity; the top is composed of a loose sequence of columnar crystals, and many ungrown secondary dendrites constitute the "cauliflower head" area; the coating material has both excellent high-temperature phase stability and good mechanical properties, which is of great significance to the development and application of advanced structure ultra-high temperature thermal barrier coating technology. However, the antioxidant properties and adhesion of the ceramic coating prepared by the above technical solution need to be further improved; for this reason, the present invention provides an ultra-high temperature carbon-based high entropy ceramic coating and a preparation method to solve the above-mentioned improvement problems. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides an ultra-high temperature carbon-based high entropy ceramic coating and a preparation method thereof, which solves the problems mentioned in the above background technology.
[0004] To achieve the above objectives, the present invention is implemented by the following technical solutions: an ultra-high temperature carbon-based high entropy ceramic coating, the ceramic coating comprising the following components: a mixed slurry, a rare earth oxide, a metal oxide, and fluorinated graphene oxide; Among them, the rare earth oxide is selected from at least two of Y2O3, Yb2O3, Lu2O3, Eu2O3, and Er2O3; the metal oxide is selected from at least two of MgO, CoO, NiO, CuO, and ZnO.
[0005] Preferably, the preparation method of the fluorinated graphene oxide is: S1. Cool the concentrated sulfuric acid in an ice bath under stirring, add graphite fluoride and sodium nitrate in sequence, stir and react, and then slowly add potassium permanganate; S2, heating the water bath, and reacting at this temperature, then continuing to heat the water bath to react; S3, slowly add deionized water, stir the solution until the temperature drops to room temperature, and then add hydrogen peroxide dropwise under stirring; S4. Let the solution stand for stratification, remove the middle layer solution, add 5% by mass hydrochloric acid, stir, let the solution stand, and wash with deionized water until the solution is neutral to obtain fluorinated graphene oxide.
[0006] Preferably, the ratio of the added amount of each substance is concentrated sulfuric acid: graphite fluoride: potassium permanganate: deionized water: hydrogen peroxide: hydrochloric acid = (15-25) mL: (6.5-10) g: (3-5.5) g: (20-30) mL: (1.2-2) g: (8.5-12) mL.
[0007] Preferably, in the preparation process of the fluorinated graphene oxide, the stirring speed during the reaction is 250-400 r / min; in S3, the stirring speed during the dropwise addition of hydrogen peroxide is 800-1000 r / min; In S1, the temperature is lowered to 0-2°C and the stirring reaction time is 75-90 minutes; In S2, the water bath is heated to 25-35°C, the reaction is carried out for 1.5-2h, and the water bath is heated to 35-45°C, and the reaction is carried out for 45-60min; In S4, the standing time is 8-12 hours.
[0008] A method for preparing an ultra-high temperature carbon-based high entropy ceramic coating, specifically comprising the following preparation steps: Step 1: Pour phenolic resin into anhydrous ethanol, stir until completely dissolved, add SiC powder thereto, first use magnetic stirring, then use ultrasonic dispersion treatment to prepare a mixed slurry; Step 2: After the substrate is completely immersed in the mixed slurry, it is first naturally dried and then placed in a drying box, a tubular furnace and a vacuum furnace in sequence; Step 3: Weigh rare earth oxides, metal oxides, and fluorinated graphene oxide, mix them by wet ball milling, and then dry them in a drying oven. The obtained mixed powder is pre-sintered, crushed, and granulated again, and then deposited on the surface of the substrate by plasma spray physical vapor deposition technology to obtain an ultra-high temperature carbon-based high-entropy ceramic coating.
[0009] Preferably, the mass ratio of the added amount of each substance is phenolic resin: SiC powder: rare earth oxide: metal oxide: fluorinated graphene oxide = (8.5-12): (5.5-9): (22-28): (15-20): (40-45).
[0010] Preferably, in step 1, the magnetic stirring time is 15-30 min, and the ultrasonic dispersion treatment time is 25-35 min.
[0011] Preferably, in step 2, the dipping time is 2-4 seconds, the temperature of the drying box is 150-180° C., and the drying time is 3-4 hours; The temperature of the vacuum furnace is 1700-1900°C, the heating rate is 5-10°C / min, and after the heating is completed, it is kept warm for 15-30 minutes and then cooled to room temperature along with the furnace; Inert gas is introduced into the tubular furnace for protection. The temperature of the tubular furnace is 700-900° C., and after heating, the temperature is kept for 120-150 minutes.
[0012] Preferably, in step three, the temperature of the drying oven is 110-120°C, and the pre-sintering temperature is 1500-1600°C.
[0013] Beneficial Effects The present invention provides an ultra-high temperature carbon-based high entropy ceramic coating and a preparation method thereof. Compared with the prior art, it has the following beneficial effects: (1) The ultra-high temperature carbon-based high entropy ceramic coating and preparation method, by immersing the substrate in the mixed slurry, thereby forming a dense protective film on its surface, which can effectively improve the wear resistance of the substrate, and at the same time can block the erosion of the substrate by the external corrosive medium, and protect the substrate from corrosion; and the phenolic resin can well infiltrate the substrate, and at the same time can also bond the silicon carbide particles together and attach them to the surface of the substrate, so that the bond between the coating and the substrate is relatively firm, thereby improving the adhesion of the coating; at the same time, the phenolic resin can be carbonized at high temperature to form a carbonaceous structure, which has a certain high temperature stability, and silicon carbide itself is also a high temperature resistant material, so the ceramic coating can maintain good performance in a high temperature environment, preventing the substrate from being oxidized or damaged at high temperature. (2) The ultra-high temperature carbon-based high entropy ceramic coating and its preparation method, due to the good thermal stability of rare earth oxides, can prevent the grain growth of the ceramic coating and inhibit the thermal decomposition of the coating under high temperature environment, thereby maintaining the structural integrity of the coating; metal oxides also have a certain high temperature resistance, and synergistically with rare earth oxides, the coating can maintain stable performance under high temperature conditions; at the same time, metal oxides can increase the hardness of the coating, making the coating surface harder and resistant to friction and wear. Fluorinated graphene oxide has good lubrication properties. When the coating surface is rubbed, it can reduce friction and wear, further improving the wear resistance of the coating; rare earth oxides can improve the chemical stability of the ceramic coating, and can form a protective film on the coating surface to block the erosion of corrosive media. The chemical properties of the metal oxides themselves also help to enhance the corrosion resistance of the coating, prevent the base material from being corroded, and further improve the corrosion resistance of the coating; as an important component of the ceramic coating, metal oxides can significantly improve the hardness of the coating, and rare earth oxides can play a role of dispersion strengthening, making the crystal structure inside the coating more compact, thereby improving the strength of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a comparison chart of the high temperature resistance performance test provided by the present invention. DETAILED DESCRIPTION
[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] Example 1 A method for preparing an ultra-high temperature carbon-based high entropy ceramic coating, specifically comprising the following preparation steps: Step 1: Pour 8.5 g of phenolic resin into 30 mL of anhydrous ethanol, stir until completely dissolved, add 5.5 g of SiC powder, stir magnetically for 15 min, and then perform ultrasonic dispersion treatment for 25 min to obtain a mixed slurry; Step 2: After the substrate is completely immersed in the mixed slurry for 2 seconds, it is first naturally dried, then placed in a drying oven at 150°C for 3 hours, and then placed in a tubular furnace protected by an inert atmosphere and heated to 700°C, then kept warm for 120 minutes, and finally placed in a vacuum furnace, heated to 1700°C at a heating rate of 5°C / min, and then kept warm for 15 minutes, and then cooled to room temperature with the furnace; Step 3, weigh 22g of rare earth oxide, 15g of metal oxide, and 40g of fluorinated graphene oxide, and mix them by wet ball milling, and then dry them in a drying oven at 110°C. The obtained mixed powder is pre-sintered at a temperature of 1500°C, crushed, and granulated again, and then deposited on the surface of the substrate by plasma spray physical vapor deposition technology to obtain an ultra-high temperature carbon-based high-entropy ceramic coating; The rare earth oxides are Y2O3 and Yb2O3, and the mass ratio thereof is 1:1; the metal oxides are MgO and CoO, and the mass ratio thereof is 1:1; The preparation method of fluorinated graphene oxide is as follows: at a stirring speed of 250 r / min, 15 mL of concentrated sulfuric acid is cooled to 0°C by an ice bath, and 6.5 g of graphite fluoride and sodium nitrate are added in sequence, stirred and reacted for 75 minutes, and then 3 g of potassium permanganate is slowly added; the water bath is heated to 25°C, and the reaction is carried out at this temperature for 1.5 hours, and then the water bath is continued to be heated to 35°C, and the reaction is continued at this temperature for 45 minutes; 20 mL of deionized water is slowly added, the solution temperature is stirred to drop to room temperature, and then 1.2 g of hydrogen peroxide is added dropwise at a stirring speed of 800 r / min; it is allowed to stand for 8 hours, and after the solution is separated, the middle layer solution is absorbed, and then 8.5 mL of hydrochloric acid with a mass fraction of 5% is added, stirred, allowed to stand, and washed with deionized water until the solution is neutral, so as to obtain fluorinated graphene oxide.
[0017] Example 2 A method for preparing an ultra-high temperature carbon-based high entropy ceramic coating, specifically comprising the following preparation steps: Step 1: Pour 10 g of phenolic resin into 32 mL of anhydrous ethanol, stir until completely dissolved, add 7 g of SiC powder, stir magnetically for 20 min, and then perform ultrasonic dispersion treatment for 30 min to obtain a mixed slurry; Step 2: After the substrate is completely immersed in the mixed slurry for 3 seconds, it is first naturally dried, then placed in a drying oven at 160°C for 3.5 hours, and then placed in a tubular furnace protected by an inert atmosphere and heated to 800°C, then kept warm for 130 minutes, and finally placed in a vacuum furnace, heated to 1800°C at a heating rate of 6°C / min, and then kept warm for 20 minutes, and then cooled to room temperature with the furnace; Step 3, weigh 25g of rare earth oxide, 18g of metal oxide, and 42g of fluorinated graphene oxide, and mix them by wet ball milling, and then place them in a drying oven at 115°C to dry. The obtained mixed powder is pre-sintered at a temperature of 1550°C, crushed, and granulated again, and then deposited on the surface of the substrate by plasma spray physical vapor deposition technology to obtain an ultra-high temperature carbon-based high entropy ceramic coating; The rare earth oxides are Yb2O3 and Lu2O3, and the mass ratio thereof is 1:1; the metal oxides are CoO and NiO, and the mass ratio thereof is 1:1; The preparation method of fluorinated graphene oxide is as follows: at a stirring speed of 300 r / min, 20 mL of concentrated sulfuric acid is cooled to 1°C by an ice bath, and 8 g of graphite fluoride and sodium nitrate are added in sequence, stirred and reacted for 80 minutes, and then 4 g of potassium permanganate is slowly added; the water bath is heated to 30°C, and the reaction is carried out at this temperature for 1.8 hours, and then the water bath is heated to 40°C, and the reaction is continued for 50 minutes at this temperature; 25 mL of deionized water is slowly added, the solution temperature is stirred to drop to room temperature, and then 1.6 g of hydrogen peroxide is added dropwise at a stirring speed of 900 r / min; it is allowed to stand for 10 hours, and after the solution is separated into layers, the middle layer solution is absorbed, and then 10 mL of hydrochloric acid with a mass fraction of 5% is added, stirred, allowed to stand, and washed with deionized water until the solution is neutral, so as to obtain fluorinated graphene oxide.
[0018] Example 3 A method for preparing an ultra-high temperature carbon-based high entropy ceramic coating, specifically comprising the following preparation steps: Step 1: Pour 12 g of phenolic resin into 35 mL of anhydrous ethanol, stir until completely dissolved, add 9 g of SiC powder, stir magnetically for 30 min, and then perform ultrasonic dispersion treatment for 35 min to obtain a mixed slurry; Step 2: After the substrate is completely immersed in the mixed slurry for 4 seconds, it is first naturally dried, then placed in a drying oven at 180°C for 4 hours, and then placed in a tubular furnace protected by an inert atmosphere and heated to 900°C, then kept warm for 150 minutes, and finally placed in a vacuum furnace, heated to 1900°C at a heating rate of 10°C / min, and then kept warm for 30 minutes, and then cooled to room temperature with the furnace; Step 3: Weigh 28 g of rare earth oxide, 20 g of metal oxide, and 45 g of fluorinated graphene oxide, mix them by wet ball milling, and then dry them in a drying oven at 120°C. The obtained mixed powder is pre-sintered at 1600°C, crushed, and granulated again, and then deposited on the surface of the substrate by plasma spray physical vapor deposition technology to obtain an ultra-high temperature carbon-based high-entropy ceramic coating; The rare earth oxides are Eu2O3 and Er2O3, and the mass ratio thereof is 1:1; the metal oxides are CuO and ZnO, and the mass ratio thereof is 1:1; The preparation method of fluorinated graphene oxide is as follows: at a stirring speed of 400 r / min, 25 mL of concentrated sulfuric acid is cooled to 2°C by an ice bath, and 10 g of graphite fluoride and sodium nitrate are added in sequence, stirred and reacted for 90 minutes, and then 5.5 g of potassium permanganate is slowly added; the water bath is heated to 35°C, and the reaction is carried out at this temperature for 2 hours, and then the water bath is continued to be heated to 45°C, and the reaction is continued at this temperature for 60 minutes; 30 mL of deionized water is slowly added, the solution temperature is stirred to drop to room temperature, and then 2 g of hydrogen peroxide is added dropwise at a stirring speed of 1000 r / min; it is allowed to stand for 12 hours, and after the solution is layered, the middle layer solution is absorbed, and then 12 mL of hydrochloric acid with a mass fraction of 5% is added, stirred, allowed to stand, and washed with deionized water until the solution is neutral, so as to obtain fluorinated graphene oxide.
[0019] Comparative Example 1 Compared with Example 1, the difference is that the mixed slurry is deleted; the rest remains unchanged.
[0020] Comparative Example 2 Compared with Example 1, the difference is that the fluorinated graphene oxide is replaced by graphene; the rest remains unchanged.
[0021] Comparative Example 3 Compared with Example 1, the difference is that no metal oxide is added; the rest remains unchanged.
[0022] Coating wear resistance test: The friction test was carried out using the Zhongke Kaihua HT-1000 ball-disc friction tester. A SiN4 ceramic ball with a diameter of 4 mm was used as the grinding material for the friction test. The load applied in the friction test was 5 N, the friction speed was 0.5 m / s, and the friction duration was 30 min. After the experiment, the wear amount was measured using an optical profilometer. The results are shown in Table 1.
[0023] Coating Vickers hardness test: The test was carried out in accordance with GB / T2848-1992, using an HV-50 Vickers hardness tester, a load of 300N, a holding time of 15s, and measuring the diagonal length of the indentation through the eyepiece cursor; the results are shown in Table 1.
[0024] Coating oxidation resistance test: The coating sample was placed in alumina and then placed in a furnace. The sample was heated to the set temperature with the furnace and then kept warm. The sample was oxidized in air at 1000°C for 347h and 468h respectively, with a heating rate of 10°C / min. The sample was naturally cooled to room temperature with the furnace. Subsequently, the oxidized sample was weighed with an analytical balance, and the mass change percentage of the sample was calculated (the results are shown in Table 1): ; In the formula, is the percentage change in mass of the sample; is the mass of the sample before oxidation, g; is the mass of the sample after oxidation, g.
[0025] Coating adhesion test: Test according to GB / T9286-1998, the 100-grid cutter tooth pitch is 2mm, and the test results are graded against the standard grade.
[0026] Table 1 Coating high temperature resistance test: The sample was thermally cycled 10 times under the condition of 1400℃-200s; the results are as follows Figure 1 As shown: slight cracks appeared on the surface of the samples of Examples 1-3, which were not obvious; the cracks on the surface of Comparative Examples 1-3 gradually increased.
[0027] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0028] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An ultra-high temperature carbon-based high entropy ceramic coating, characterized in that: The ceramic coating comprises the following components: mixed slurry, rare earth oxide, metal oxide, and fluorinated graphene oxide; Among them, the rare earth oxide is selected from at least two of Y2O3, Yb2O3, Lu2O3, Eu2O3, and Er2O3; the metal oxide is selected from at least two of MgO, CoO, NiO, CuO, and ZnO.
2. The ultra-high temperature carbon-based high entropy ceramic coating according to claim 1, characterized in that: The preparation method of the fluorinated graphene oxide is: S1. Cool the concentrated sulfuric acid in an ice bath under stirring, and add graphite fluoride and sodium nitrate in sequence. After stirring for reaction, slowly add potassium permanganate; S2, heating the water bath, and reacting at this temperature, then continuing to heat the water bath to react; S3, slowly add deionized water, stir the solution until the temperature drops to room temperature, and then drop hydrogen peroxide under stirring; S4. Let the solution stand for stratification, remove the middle layer solution, add 5% by mass hydrochloric acid, stir, let the solution stand, and wash with deionized water until the solution is neutral to obtain fluorinated graphene oxide.
3. The ultra-high temperature carbon-based high entropy ceramic coating according to claim 2, characterized in that: in, The ratio of the added amount of each substance is concentrated sulfuric acid: graphite fluoride: potassium permanganate: deionized water: hydrogen peroxide: hydrochloric acid = (15-25) mL: (6.5-10) g: (3-5.5) g: (20-30) mL: (1.2-2) g: (8.5-12) mL.
4. The ultra-high temperature carbon-based high entropy ceramic coating according to claim 2, characterized in that: During the preparation of the fluorinated graphene oxide, the stirring speed during the reaction is 250-400 r / min; in S3, the stirring speed during the dropwise addition of hydrogen peroxide is 800-1000 r / min; In S1, the temperature is lowered to 0-2°C and the stirring reaction time is 75-90 minutes; In S2, the water bath is heated to 25-35°C, the reaction is carried out for 1.5-2h, and the water bath is further heated to 35-45°C, and the reaction is carried out for 45-60min; In S4, the standing time is 8-12 hours.
5. A method for preparing an ultra-high temperature carbon-based high entropy ceramic coating according to claim 1, characterized in that: The specific preparation steps include: Step 1: Pour phenolic resin into anhydrous ethanol, stir until completely dissolved, add SiC powder thereto, first use magnetic stirring, then use ultrasonic dispersion treatment to prepare a mixed slurry; Step 2: After the substrate is completely immersed in the mixed slurry, it is first naturally dried and then placed in a drying box, a tubular furnace and a vacuum furnace in sequence; Step 3: Weigh rare earth oxides, metal oxides, and fluorinated graphene oxide, mix them by wet ball milling, and then dry them in a drying oven. The obtained mixed powder is pre-sintered, crushed, and granulated again, and then deposited on the surface of the substrate by plasma spray physical vapor deposition technology to obtain an ultra-high temperature carbon-based high-entropy ceramic coating.
6. The method for preparing an ultra-high temperature carbon-based high entropy ceramic coating according to claim 5, characterized in that: The mass ratio of the added amount of each substance is phenolic resin: SiC powder: rare earth oxide: metal oxide: fluorinated graphene oxide = (8.5-12): (5.5-9): (22-28): (15-20): (40-45).
7. The method for preparing an ultra-high temperature carbon-based high entropy ceramic coating according to claim 5, characterized in that: In the step 1, the magnetic stirring time is 15-30 min, and the ultrasonic dispersion treatment time is 25-35 min.
8. The method for preparing an ultra-high temperature carbon-based high entropy ceramic coating according to claim 5, characterized in that: In the step 2, the dipping time is 2-4 seconds, the temperature of the drying oven is 150-180°C, and the drying time is 3-4 hours; The temperature of the vacuum furnace is 1700-1900°C, the heating rate is 5-10°C / min, and after the heating is completed, it is kept warm for 15-30 minutes and then cooled to room temperature along with the furnace; Inert gas is introduced into the tubular furnace for protection. The temperature of the tubular furnace is 700-900° C., and after heating, the temperature is kept for 120-150 minutes.
9. The method for preparing an ultra-high temperature carbon-based high entropy ceramic coating according to claim 5, characterized in that: In the step 3, the temperature of the drying oven is 110-120°C, and the pre-sintering temperature is 1500-1600°C.
Citation Information
Patent Citations
High-temperature-resistant long-service-life composite coating on surface of carbon / carbon composite material and preparation method
CN113387724A
High-entropy ceramic thermal barrier coating and preparation method thereof
CN116377372A
High-entropy carbide ceramic-based nano composite cutter material and preparation method thereof
CN118580078A
High-entropy oxide ceramic capable of improving crack resistance and preparation method of high-entropy oxide ceramic
CN118791285A
Ceramic gel phase change energy storage coating and preparation method thereof
CN119101378A